2001
DOI: 10.1021/ic001185d
|View full text |Cite
|
Sign up to set email alerts
|

Models for Extradiol Cleaving Catechol Dioxygenases:  Syntheses, Structures, and Reactivities of Iron(II)−Monoanionic Catecholate Complexes

Abstract: Crystallographic and spectroscopic studies of extradiol cleaving catechol dioxygenases indicate that the enzyme-substrate complexes have both an iron(II) center and a monoanionic catecholate. Herein we report a series of iron(II)-monoanionic catecholate complexes, [(L)Fe(II)(catH)](X) (1a, L = 6-Me(3)-TPA (tris(6-methyl-2-pyridylmethyl)amine), catH = CatH (1,2-catecholate monoanion); 1b, L = 6-Me(3)-TPA, catH = DBCH (3,5-di-tert-butyl-1,2-catecholate monoanion); 1c, L = 6-Me(2)-bpmcn (N,N'-dimethyl-N,N'-bis(6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
125
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 57 publications
11
125
0
Order By: Relevance
“…Despite a common peroxo intermediate structure, the two enzyme classes differ in the type of metal center to which the peroxo intermediate is co (34,36,43). It has also been suggested that the precise stereochemistry of the metal-peroxo-substrate unit determines the sites of cleavage (13).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a common peroxo intermediate structure, the two enzyme classes differ in the type of metal center to which the peroxo intermediate is co (34,36,43). It has also been suggested that the precise stereochemistry of the metal-peroxo-substrate unit determines the sites of cleavage (13).…”
Section: Discussionmentioning
confidence: 99%
“…UV-visible spectra (not shown) revealed three bands at 310, 365, and 400 nm, characteristic of charge-transfer bands observed with small NO-iron complexes (35)(36)(37)(38). The appearance of these bands grew in parallel with the increase of the EPR signal intensity.…”
Section: No Binds To Fe II In Fefur To Form a S ‫؍‬ 1͞2 Dimeric Speciesmentioning
confidence: 95%
“…The addition of NO gas to an anaerobic solution of FeFur resulted in immediate change from colorless to yellow-green, associated to the appearance of absorption bands in the UV-visible spectra as well as a g ϭ 2.03 EPR signal. Both features are characteristics of NO-iron complexes (34)(35)(36)(37)(38). The rate of NO complex formation was controlled by the decomposition of DEANO (t 1/2 ϭ 15 min at 20°C, pH 7.5).…”
Section: No Binds To Fe II In Fefur To Form a S ‫؍‬ 1͞2 Dimeric Speciesmentioning
confidence: 99%
“…This coordination mode is now well established in the chemistry of substituted TPA ligands and obviously reflects a gain in stability with respect to a more sterically hindered environment. [12,24,30] The 1 H NMR spectra of the FeCl 3 complexes generally display broad and unresolved signals in the paramagnetic region. [24,25] Complex 1, with an almost silent trace, is no exception to this rule.…”
mentioning
confidence: 99%
“…[2,20,21,30] An iron(ii)-TPA complex in which a thiolate is coordinated to the metal has been found to react rapidly with dioxygen. [32] The redox potential for this complex is not available, but as it is a cationic species the value is likely to be positive.…”
mentioning
confidence: 99%